2009
DOI: 10.1007/s00417-009-1036-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of latanoprost in eyes with uveitic glaucoma

Abstract: Latanoprost is safe and equally effective to a fixed combination of dorzolamide and timolol in the treatment of uveitic glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…However, this potential seems to be more of a theoretical than an actual concern, and in humans the available evidence is solidly in favor of using these drugs when necessary in patients with uveitic glaucoma. [45][46][47] Evidence is more limited in dogs but also supports their use. 48,49 In humans, uveitic glaucoma often fails to respond to medical management alone, and the same may be true in veterinary patients.…”
Section: Treatmentmentioning
confidence: 93%
See 1 more Smart Citation
“…However, this potential seems to be more of a theoretical than an actual concern, and in humans the available evidence is solidly in favor of using these drugs when necessary in patients with uveitic glaucoma. [45][46][47] Evidence is more limited in dogs but also supports their use. 48,49 In humans, uveitic glaucoma often fails to respond to medical management alone, and the same may be true in veterinary patients.…”
Section: Treatmentmentioning
confidence: 93%
“…6 Animals with secondary glaucoma may require more diagnostic testing than animals with primary glaucoma, and a thorough physical examination is crucial. Highresolution ocular ultrasonography (20 MHz) and ultrasonography biomicroscopy (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) are frequently helpful when evaluating a dog with suspected secondary glaucoma, particularly in cases in which dense corneal edema, hyphema, or other abnormalities preclude visualization of the interior of the eye. Other animals may benefit from additional imaging such as thoracic radiographs or abdominal ultrasonography; serology; cytology; or other laboratory testing.…”
mentioning
confidence: 99%
“…Although the use of prostaglandin analogues was previously suspected of inciting inflammation in glaucoma patients to the extent that its use has been contraindicated in UG, the risk of inducing an episode of uveitis is low, and some studies have suggested similar efficacy to a fixed combination of dorzolamide and timolol [66], despite concerns that there may be lower efficacy in a condition where prostaglandins are already present in the eye. The use of topical prostaglandin analogues in uveitic eyes has been shown to significantly reduce the IOP without inciting an increased risk of CME or anterior uveitis [13,67].…”
Section: Prostaglandin Analoguesmentioning
confidence: 99%
“…Higher rates are reported in those with rheumatoid arthritis-associated iridocyclitis, Fuchs heterochromic iridocyclitis (27%), sarcoidosis (34%), herpes simplex keratouveitis (54%), zoster uveitis (38%), Lyme-associated uveitis, cancer-associated uveitis 13 , juvenile idiopathic arthritis (12-35%), Behçet's disease, pars planitis, sympathetic ophthalmia, and syphilis 110 . About 30% of eyes with UG may require surgery after initial medical treatment [111][112][113] . There is a consensus that the surgical success rate of filtering surgery is lower for eyes with UG compared with POAG.…”
Section: Uveitic Glaucoma (Ug)mentioning
confidence: 99%